1989
DOI: 10.1182/blood.v73.5.1279.1279
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of the interleukin-6 gene in chronic lymphocytic leukemia

Abstract: Interleukin-6 (IL-6) is a pleiotropic lymphokine active as a growth factor on B-cell hybridomas and plasmacytomas and found to be identical with B-cell stimulatory factor 2, interferon beta 2, 26-Kd protein, and hepatocytes stimulating factor. IL-6 gene expression was investigated in fresh human chronic lymphocytic leukemia (B-CLL) and in acute lymphoblastic leukemia (ALL) by Northern blot analysis using a specific cDNA probe. 1.3-kb IL-6 transcript was found in six out of 11 B-CLL patients, while no hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…A possible autocrine role for IL-6 was also reported in non-Hodgkins lymphomas, chronic lymphocytic leukemias and acute myeloid leukemias [79, IL-6 was also demonstrated to be an autocrine growth factor for EBV-transformed B cell lines [89] and expression of an exogenous IL-6 gene in these B cell lines conferred growth advantage and in vivo tumorigenicity [90]. However, it has been controversial whether all myeloma cells actually produce IL-6, because only some myeloma cell lines were found to produce IL-6 [76,91-931, and bone marrow-adherent cells (rather than bone marrow nonadherent cell populations [86][87][88].…”
Section: Il-6 Is a Growth Factor For Plasmacytoma/myelomamentioning
confidence: 99%
“…A possible autocrine role for IL-6 was also reported in non-Hodgkins lymphomas, chronic lymphocytic leukemias and acute myeloid leukemias [79, IL-6 was also demonstrated to be an autocrine growth factor for EBV-transformed B cell lines [89] and expression of an exogenous IL-6 gene in these B cell lines conferred growth advantage and in vivo tumorigenicity [90]. However, it has been controversial whether all myeloma cells actually produce IL-6, because only some myeloma cell lines were found to produce IL-6 [76,91-931, and bone marrow-adherent cells (rather than bone marrow nonadherent cell populations [86][87][88].…”
Section: Il-6 Is a Growth Factor For Plasmacytoma/myelomamentioning
confidence: 99%
“…Changes in the cytokine network between malignant cells and residual T lymphocytes could sustain the expansion of the leukaemic B-cell clone. Accordingly, there is evidence to suggest that cytokines may participate in auto/paracrine loops affecting CLL cell growth (Digel et al, 1989;Foa et al, 1990;Biondi et al, 1989;Aguilar-Santelises et al, 1991;Aderka et al, 1993;Francia di Celle et al, 1994). The expression of cytokine receptors, such as the high-affinity interleukin 2 (IL2) receptor (R) complex a, b, g (de Totero et al, 1995), on CLL cells but not on normal resting B cells, further supports this contention.…”
mentioning
confidence: 99%
“…Recently, Freeman et al (1989) observed IL-6 gene expression in several B cell malignancies, but not in B-CLL. In contrast, Biondi et al (1989) found that B cells from a significant proportion of B-CLL patients constitutively express IL-6 gene and secrete variable amounts ofthe biologically active protein.…”
Section: Discussionmentioning
confidence: 90%